REGULATION OF CONSULTING SERVICES BASED ON DIGITAL TECHNOLOGIES: CIVIL LAW ASPECTS - Shahriddin Fakhriddin Ugli Asadov (International Journal of Artificial Intelligence for Digital Marketing, 2025)
Objective: This study aims to analyze the civil legal framework regulating consulting services based on digital technologies, with a focus on the legal challenges emerging from the transition from traditional to digital platforms in Uzbekistan. Method: Employing systematic, comparative legal, and statistical analyses, the research examines electronic contracts, the rights and obligations of parties, and mechanisms for dispute resolution within the context of Uzbekistan's "Digital Uzbekistan – 2030" strategy. Results: The findings reveal significant gaps in existing regulations concerning service quality, confidentiality, and liability in digital consulting services. The study proposes legislative reforms, including amendments to the Civil Code and the Law "On Electronic Commerce," alongside recommendations for the development of a specialized law on consulting services. Additionally, institutional improvements such as certification systems for digital platforms and the establishment of quality standards are suggested to strengthen regulatory oversight. Novelty: This research contributes novel insights by highlighting the specific legal challenges of digital consulting services in Uzbekistan and offering comprehensive legal and institutional reform strategies to foster consumer protection and support the growth of digital consulting within the rapidly evolving digital economy.